Kids Farming for the Initiation of Love for Agriculture and the Environment - Mohammad Natsir; Irmawanty Irmawanty; Sri Mardiyati (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Community service programs through Kids Farming for the initiation of love for agriculture and the environment aim to, among others: (1) increase children's understanding and insight into the importance of agriculture in the future and modern agriculture, (2) improve children's skills in planting practices, (3) increase responsible attitudes and love for agriculture in children, (4) increase students' knowledge about the importance of environmental conservation, and environmentally friendly agriculture (zero waste), (5) increase responsible and environmentally loving attitudes in children. To achieve the expected goals and output targets, the implementation method used in this program is a fun learning method through training and mentoring of children. This program has stages in the implementation of activities, including: preparation, interactive learning, planting, mentoring, and follow-up. The results of the implementation of this program include: (1) the formation of teamwork in children students to strengthen togetherness and erode individualism, (2) the formation of student character expression by loving the world of agriculture more and environmental preservation through green lifestyle, (3) the formation of concern for the surrounding environment, (4) a change in mindset towards stereotypes of the agricultural world, so as to change ideals closer to the world of agriculture.